2010
DOI: 10.1111/j.1439-0531.2010.01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Detection of Iraqi Riverine Buffalo (Bubalus bubalis) Using the BioPRYN Enzyme‐Linked Immunosorbent Assay for PSPB and the Progesterone Assay

Abstract: This study was undertaken to detect pregnancy in Iraqi riverine buffalo (Bubalus bubalis) using three different methods (rectal palpation, plasma progesterone concentration and detection of the presence of pregnancy-specific protein B (PSPB) with the BioPRYN(®) enzyme-linked immunosorbent assay (ELISA) test. The aim of the study was to identify the most sensitive, early and accurate method for detecting pregnancy. Twenty-two female riverine buffalo that were 6.0 ± 0.93 years old were used. Four blood samples p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Dairy cattle studies using a PSPB ELISA test for pregnancy detection showed a sensitivity of 93.9% and specificity of 95.5% on day 28, while the overall accuracy at days 28, 30 and 35 was 94.7% (Romano & Larson, ). The specificity results in this study are similar to the data from both domestic cattle and Iraqi water buffalo (Abdulkareem et al., ; Romano & Larson, ). The lower sensitivity results in this study when compared to other bovid studies could likely be explained by sampling times relative to breeding dates.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Dairy cattle studies using a PSPB ELISA test for pregnancy detection showed a sensitivity of 93.9% and specificity of 95.5% on day 28, while the overall accuracy at days 28, 30 and 35 was 94.7% (Romano & Larson, ). The specificity results in this study are similar to the data from both domestic cattle and Iraqi water buffalo (Abdulkareem et al., ; Romano & Larson, ). The lower sensitivity results in this study when compared to other bovid studies could likely be explained by sampling times relative to breeding dates.…”
Section: Discussionsupporting
confidence: 91%
“…This correlates with a previous study using PSP‐RIA in wild wood bison, showing an overall accuracy of 95% (Haigh et al., ). A study using this specific PSPB ELISA test (BioPRYN ® ) in captive Iraqi water buffalo showed a sensitivity of 88.88% on days 22–24 post‐mating, which increased to 100% after 32 days post‐mating; the specificity data in this same study were 76.92% at days 22–24 post‐mating, but increased to 92.31% at days 32–34 and subsequently to 100% after day 58 post‐mating (Abdulkareem et al., ). Dairy cattle studies using a PSPB ELISA test for pregnancy detection showed a sensitivity of 93.9% and specificity of 95.5% on day 28, while the overall accuracy at days 28, 30 and 35 was 94.7% (Romano & Larson, ).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations